Basic Khmer - Sok, Vathanak (Open textbook library., 2022)
This online interactive theme-based open textbook is for beginner learners of the Khmer language. This book aims to provide a practical introduction to speaking, listening, and reading. By the end of this course, students will be at the B1 level of the Common Framework for Language and at the low intermediate level on the American Council on the Teaching of Foreign Languages (ACTFL) proficiency scales. Basic Khmer is funded by the Open Educational Resources Program at Michigan State University.